ANALISIS PENGARUH VARIABEL MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) - Indah Yuliana (lp2m-uin malang, 2007)
The investment growth in a country influenced by its economic growth. The higher economic growth of a country, the better prosperity of country’s people. The better prosperity is signed by the improvement of people income. It means that a larger opportunity of investment. The performance development of a company affected by internal and external factor. External factor shows that the situation of country especially involving economic, political, and social factors. The economic growth of a country can be seen from economical macro condition, including the amount of spreading money, Indonesian interest rate, and rupiah exchange. The purposes of this research are (1) to find out a macro variable (the amount of spreading money, the level of interest rate, and exchange value) to the joint stock market price index in Indonesian Stock Market, (2) to find out a dominant influence of macro variable indicator (the amount of spreading money, inflation, the level of Indonesian interest rate, exchange value) to the joint stock market in Indonesian Stock Market. This research is a quantitative research by using a descriptive method Data uses a secondary data such as the amount of spreading money, inflation, the level of Indonesian interest rate, exchange value and the joint stock market price index over the periods 2001-2007. Data collecting method is data by documentation. Data analysis method uses a double regression liner.The result of this research shows that there is a simultaneous economical macro variable to the joint stock market price index in Indonesian Stock Market. It is proven by Ftest is 434.723 Ftable 1.960 with level of significant 5%. The macro variable influence to the joint stock market price index is 95.7%, meanwhile the remains is affected by another variable out of the model. Partially, the amount of spreading money affects dominantly to the joint stock market price index in Indonesian Stock Market. Key Words: The Amount of Spreading Money, Inflation, The Level of Indonesian Interest Rate, Exchange Value of Rupiah, and The Joint Stock Market Price Index